Intervensi Keperawatan "Peningkatan Perfusi Jaringan Perifer Pada Pasien Ulkus Diabetik: Laporan Kasus - Ismail Ismail; Baharuddin K; Sukriyadi Sukriyadi; Muhammad Basri; Nasrullah Nasrullah; Sukma Saini (Media Kesehatan Politeknik Kesehatan Makassar, 2023)
Changes in peripheral tissue perfusion in diabetic wounds are important because they can affect the wound healing process, increase the risk of infection, and inhibit healing in individuals with diabetes. This study aims to describe a nursing intervention for increased peripheral tissue perfusion in type 2 Diabetes Mellitus (DM) patients with leg wound complications. This study is a case report of nursing intervention. DM patients treated in the general wound care room of a hospital in Makassar 13 – 17 May 2023. This study found impaired peripheral tissue perfusion as a result of damage to blood vessels (angiopathy), especially to capillaries. In addition, neuropathy or nerve damage in diabetes can also affect the regulation of blood flow to the extremities (such as the feet) which can interfere with the body's mechanism of responding to changes in blood flow. We implement professional treatment strategies to improve tissue perfusion through controlling blood sugar within normal ranges to prevent vascular damage, measuring blood pressure, controlling blood pressure to remain stable to protect blood vessels, adequate hydration to ensure patients are well hydrated to maintain smooth blood flow, Regular exercise through regular physical activity to improve blood flow and help repair condition of blood vessels, proper wound care by cleaning and treating wounds periodically to prevent infection and accelerate healing.